Tingkat Kecemasan Nyeri Jahitan Perineum Pada Ibu Post Partum Dengan Mobilisasi Dini Di Puskesmas PONED Sikumana Kota Kupang - Atalia Pili Mangngi (Pusat riset dan Inovasi Nasional, 2022)
The post partum period is a sensitive period for mothers which will affect newborn care. Mother's anxiety and fear because she is afraid of stitches that arise causes her not to mobilize early. The most important thing at this time is that midwives provide support on an ongoing basis according to the mother's needs to reduce physical and psychological tension during the postpartum period. This study aims to prove the anxiety level of perineal suture pain in post partum mothers regarding mobilization. This study used an analytic survey with a cross-sectional research design. The data collection technique was carried out by observation, namely data collection on anxiety levels was taken using the Hamilton Rating Scale for Axsiety (HRS-A) while data for perineal suture pain was obtained from a pain level questionnaire. The population was taken with a total of 37 post partum mothers and a total sample of 22 post partum mothers.